Pengaruh Kepemimpinan Transformasional terhadap Keinovatifan Guru SMA Negeri Kota Lubuklinggau - Donni Pestalozi; Rudi Erwandi; M Rusni Eka Putra (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this study is to find out whether there is a direct positive relationship between teachers of public high schools in the city of Lubuklinggau. This study was designed using a survey method and in data collection using a questionnaire. The sample in this study were 38 teachers from Public High Schools in the city of Lubuklinggau. The results of this study indicate that there is a positive direct effect of transformational leadership on innovation. The conclusions from this study are the results of the transformation of effective principals, the innovation of high teachers. Keywords: Influence, Transparency of Leadership, Innovation, Teacher.